Peran Komunitas Tjimahi Heritage dalam Melestarikan Warisan Budaya - Muhamad Rajib Alparisi; Heny Gustini Nuraeni (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
The purpose of this research is to find out how the Tjimahi Heritage community effort in empowering the community through preservation of cultural heritage, how the Tjimahi Heritage community program in empowering the community through preservation of cultural heritage, and the results of community empowerment through preservation of cultural heritage. This research method use qualitative research methods with a descriptive approach. The results of this study indicate that the Tjimahi Heritage community seeks to educate and make people aware through the preservation of cultural heritage. Various programs carried out by the Tjimahi Heritage community to empower people through the preservation of cultural heritage by discussion, exploring, and becoming partners of activities related to history and preservation of cultural heritage. The results obtained are that the community understands the history of their area and creates a senses of concern and love for their region. From the side of the Government of the City of Cimahi began developing military historical tourism which is an asset owned by the City of Cimahi.